Detection of ryanodine receptor G4911E and I4754M mutation sites and analysis of binding modes of diamide insecticides with RyR on Galeruca daurica (Coleoptera: Chrysomelidae) - Ren, Hao; Zhang, Hongling; Ni, Ruoyao; Li, Yanyan; Li, Ling; Wang, Wenhe; Tian, Yu; Pang, Baoping; Tan, Yao (Frontiers in Physiology, 2022)
In recent years, the leaf beetle Galeruca daurica has broken out in the northern grasslands of Inner Mongolia, its management still mainly depends on chemical control using traditional insecticides or with novel action. The study was aim to identify mutation locus associated with resistance to diamide insecticides in field population of G. daurica, to provide a reference for rational selection of insecticides and to avoid the rapid resistance development to diamide insecticides. We cloned the full length of the ryanodine receptor gene of G. daurica (GdRyR), constructed 3D model and transmembrane regions by homologous modeling based on deduced amino acid sequence. Two potential mutation loci (Gly4911Glu and Ile4754Met) and allelic mutation frequencies were detected in individuals of G. daurica. In addition, their binding patterns to two diamide insecticides (chlorantraniliprole, cyantraniliprole) were analyzed separately using a molecular docking method. The full-length cDNA sequence of GdRyR (GenBank accession number: OP828593) was obtained by splicing and assembling, which is 15,399 bp in length and encodes 5,133 amino acids. The amino acid similarity of GdRyR with that of other Coleopteran insects were 86.70%-91.33%, which possessed the typical structural characteristics. An individual resistance allelic mutation frequency test on fifty field leaf beetles has identified 12% and 32% heterozygous individuals at two potential mutation loci Gly4911Glu and Ile4754Met, respectively. The affinity of the I4754M mutant model of GdRyR for chlorantraniliprole and cyantraniliprole was not significantly different from that of the wild type, and all had non-covalent interactions such as hydrogen bonding, hydrophobic interactions and π-cation interactions. However, the G4911E mutant model showed reduced affinity and reduced mode of action with two diamide insecticides, thus affecting the binding stability of the ryanodine receptor to the diamide insecticides. In conclusion, the G4911E mutation in GdRyR may be a potential mechanism for the development of resistance to diamide insecticides on G. daurica and should be a key concern for resistance risk assessment and reasonable applications of diamide insecticides for control in future. Moreover, this study could provide a reference for ryanodine receptor structure-based insecticides design.